Donut go breaking my heart - Nelson, Suzanne, 1976- (Wish (Scholastic Inc.), 2017)
Sheyda is a tween girl who is content in behind-the-scenes roles, like helping out in the kitchen of her best friend Kiri's family's donut shop, Doughlicious. So, when Doughlicious is chosen as the site of the next movie staring tween heartthrob Cabe Sadler, and she, not Kiri, is picked to have a role in the film, Sheyda doesn't know what to think--especially when Cabe turns out to be spoiled and rude.